Endoscopic Nasobiliary Drainage in the Management of Acute Cholangitis: An Experience in 143 Patients. Issue 3 (1997) - Goenka, M. K.; Bhasin, D. K.; Kochhar, R.; Nagi, B.; Rungta, U.; Das, K.; Singh, K.
Abstract : Acute cholangitis is associated with a high mortality and morbidity and often requires drainage of the obstructed biliary system. The purpose of this study was to evaluate the usefulness and safety of endoscopic nasobiliary drainage in the treatment and prevention of acute cholangitis due to diverse etiology. During a 32-month period, 143 patients (67 males, 76 females) with age range of 15 to 84 years underwent urgent fluoroscopy guided endoscopic nasobiliary drainage using a 7 Fr catheter either to treat acute cholangitis not responding to antibiotics (group A, n = 116) or to prevent its development following endoscopic retrograde cholangiography performed in an obstructed biliary system (group B, n = 27). Underlying etiology included bile duct stones (92), malignant biliary obstruction (34), choledochal cyst (4), chronic pancreatitis (4), ruptured hydatid cyst (3), portal hypertensive cholangiopathy (3) and liver abscess (3). Endoscopic nasobiliary drainage was performed successfully in 129 patients (90.2%). Cholangitis improved within 1 to 3 days (in group A) or did not develop (in Group B) in 125 patients (96.7%) with successful endoscopic nasobiliary drainage. Two patients however required additional drainage by percutaneous transhepatic route, while two died inspite of effective endoscopic drainage. Of the 14 patients (9.8%) with failed endoscopic drainage, 9 were managed by surgical decompression or percutaneous transhepatic drainage, 3 died of septicemia. Endoscopic nasobiliary drainage is a safe and effective method to treat patients with acute cholangitis as well as to prevent its development following cholangiography performed in an obstructed biliary system.